Proceedings of the Twenty-Seventh ACM SIGMOD-SIGACT-SIGART Symposium on Principles of Database Systems 2008
DOI: 10.1145/1376916.1376953
|View full text |Cite
|
Sign up to set email alerts
|

Local Hoare reasoning about DOM

Abstract: Abstract. We provide a program logic for specifying a core subset of the sequential POSIX file system, and for reasoning abstractly about client programs working with the file system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Lowlevel imperative commands are typically local [12]. In our work on specifying DOM [7] we demonstrated that the DOM commands are also local. Here, we insist on locality.…”
Section: The Tree Fragment (Z 1[x] + Y 2[t]) Updates To (Z 1[x ⊗ 2[t]]mentioning
confidence: 81%
See 2 more Smart Citations
“…Lowlevel imperative commands are typically local [12]. In our work on specifying DOM [7] we demonstrated that the DOM commands are also local. Here, we insist on locality.…”
Section: The Tree Fragment (Z 1[x] + Y 2[t]) Updates To (Z 1[x ⊗ 2[t]]mentioning
confidence: 81%
“…It is straightforward to transfer the techniques developed here to Featherweight DOM [7]. For this paper, we have worked with the intuitive understanding of what it means for command axioms to be small.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…fragment of the W3C DOM (Gardner, Smith, Wheelhouse, and Zarfaty, 2008), and tree segments (Gardner and Wheelhouse, 2009). …”
Section: Notationmentioning
confidence: 99%
“…Context logic has been used to reason about programs that manipulate data structures, such as sequences, multisets and trees (Calcagno et al, 2007a). In particular, it has been successfully applied to reason about the W3C DOM tree update library (Gardner et al, 2008). Thus far, context logic reasoning has always been justified with respect to an operational semantics defined at the same level of abstraction as the reasoning.…”
Section: Introductionmentioning
confidence: 99%